Analysis and Prevention of SQL Injection based on Web - Li, Junfeng (Journal of Theory and Practice of Engineering Science, 2024)
With the continuous development of the network, individual or collective data are constantly generated and stored in the computer. If more private information is leaked or stolen, it will bring serious harm to individuals, families and even society. How to protect personal privacy or the security of system applications has become a top priority. Hackers on the Internet use the attack principle of different means to crack or "steal" and other malicious acts. SQL injection can be seen everywhere now, and it is also a common attack method. Knowing its principle can help us effectively prevent malicious attacks in this part.